Sensory-motor integration in Gnathonemus petersii - Skeels, SE (2022)
Animals are inundated by stimuli as they undergo the challenges of daily life. To cope, they possess senses which allow them to obtain information from their environment. They can tune into important aspects of this information and decide on the most appropriate response, requiring coordination of the animal’s sensory and motor systems. This interaction is not one directional. Animals can actively shape their perception with self-driven motion. Weakly electric fishes are an excellent group of animals to study this bidirectional interaction because they possess a unique active sensing system (their electric sense) which seems to be closely coupled with their own body movements. The aim of this thesis was to investigate sensory-motor integration in the weakly electric fish Gnathonemus petersii (G.petersii). In data chapter one, we found that electric organ discharges were generated during forwards and backwards swimming, suggesting that G.petersii have the capacity to collect electrical information bidirectionally. Importantly, we found that electrical activity generated in the two swimming modes only differed when they were investigating objects, indicating that the movements had a role in sensory acquisition. In data chapter two, we found that egocentric motion is important for object recognition, specifically movement-induced modulations (MIMs), which seem to provide information regarding an object’s shape. Lastly, we found in data chapter three that MIMs is not always a robust cue for shape recognition, especially when the objects differ subtly in shape and scanning space is compromised. Some evidence suggests that individuals might be able to use other movement related cues instead, e.g. electrical snapshots. This thesis reinforces the importance of self-generated motion in enhancing perception, especially in environments where information is difficult to extract (e.g. the murky rivers that G.petersii inhabit). These findings not only improve our understanding of active electrolocation, but of active sensing more generally.